NARRATIVE LEARNING DALAM PENDIDIKAN AGAMA ISLAM: TINJAUAN SISTEMATIS PENGEMBANGAN KARAKTER DAN EMPATI SISWA DI ERA DIGITAL - Faisol Hakim; Khotimah Suryani; Syihabuddin Qulyubi (Fakultas Keguruan dan Ilmu Pendidikan Unisda Lamongan, 2026)
Narrative learning in Islamic Religious Education (PAI) offers a pedagogically grounded pathway for developing student empathy and character, yet its evidence base remains fragmented across disciplines and has never been systematically mapped in the Indonesian context. This systematic review examines research trends in narrative learning within PAI, strategies shown effective for building empathy and character, how the digital era shapes their implementation, and gaps requiring further research. Using the PRISMA framework, five databases were searched — Google Scholar, Scopus, Crossref, Lens.org, and OpenAlex — yielding 17 articles published 2012-2026 that met the inclusion criteria. Thematic synthesis across four clusters produced four key findings. First, narrative learning is neurobiologically grounded: mirror neuron activation during storytelling establishes a direct biological mechanism for empathy development. Second, Quranic and prophetic narratives function as pedagogical resources that engage post-conventional moral reasoning. Third, digital integration in PAI character education remains exploratory, opening new narrative formats while introducing risks from unfiltered content. Fourth, no study yet integrates narrative learning, empathy development, and character formation within one validated empirical framework for PAI in Indonesia. These findings underscore the need for a digital narrative learning model explicitly targeting empathy and character within PAI.